MicroHoo: Deal failure, industry rivalry, and sources of overbidding - Aktas, Nihat; de Bodt, Eric; Roll, Richard (Journal of Corporate Finance, 2013)
On February 1, 2008, Microsoft offered $43.7billion for Yahoo. This offer was a milestone in the battle between Microsoft and Google to control the Internet search industry. The announcement accompanied a substantial decrease in Microsoft's stock price. Investors apparently considered the bid too high and doubted Microsoft's ability to create value with Yahoo's assets (the announcement combined returns implied a total value destruction of $13.29billion). Using the abnormal returns pattern of industry firms and customers, this article examines the sources of overbidding. Our analyses indicate that Microsoft's aggressive move is rooted in its rivalry with Google, but the personality traits of the involved CEOs might explain also a portion of the overbidding.